Angelo Sismonda (1807–1878), pioneer of geological mapping in the Alps of Savoy and the Piedmont: a bibliography. Issue 1 (April 2016) - Hollier, John; Blardone, Virgilio; Basaglia, Tullio; Hollier, Anita
Abstract : Angelo Sismonda (Ange Sismonda) was an Italian mineralogist and geologist based in Turin during the Risorgimento who produced pioneering maps of the Alps in the Kingdom of Sardinia. Well known during his lifetime, he is now mentioned only in passing by historians and no comprehensive bibliography of his work exists. To render his work more accessible, we present a short biography and a bibliography.